Interaction between perceived maternal care, anxiety symptoms, and the neurobehavioral response to palatable foods in adolescents. (3rd May 2016) - Machado, Tania Diniz; Dalle Molle, Roberta; Reis, Roberta Sena; Rodrigues, Danitsa Marcos; Mucellini, Amanda Brondani; Minuzzi, Luciano; Franco, Alexandre Rosa; Buchweitz, Augusto; Toazza, Rudineia; Ergang, Bárbara Cristina; Cunha, Ana Carla de Araújo; Salum, Giovanni Abrahão; et al.
Abstract: Studies in rodents have shown that early life trauma leads to anxiety, increased stress responses to threatening situations, and modifies food intake in a new environment. However, these associations are still to be tested in humans. This study aimed to verify complex interactions among anxiety diagnosis, maternal care, and baseline cortisol on food intake in a new environment in humans. A community sample of 32 adolescents and young adults was evaluated for: psychiatric diagnosis using standardized interviews, maternal care using the Parental Bonding Inventory (PBI), caloric consumption in a new environment (meal choice at a snack bar), and salivary cortisol. They also performed a brain fMRI task including the visualization of palatable foods vs. neutral items. The study found a three-way interaction between anxiety diagnosis, maternal care, and baseline cortisol levels on the total calories consumed (snacks) in a new environment. This interaction means that for those with high maternal care, there were no significant associations between cortisol levels and food intake in a new environment. However, for those with low maternal care and who have an anxiety disorder (affected), cortisol was associated with higher food intake; whereas for those with low maternal care and who did not have an anxiety disorder (resilient), cortisol was negatively associated with lower food intake. In addition, higher anxiety symptoms were associated with decreased activation in the superior and middle frontal gyrus when visualizing palatable vs. neutral items in those reporting high maternal care. These results in humans mimic experimental research findings and demonstrate that a combination of anxiety diagnosis and maternal care moderate the relationship between the HPA axis functioning, anxiety, and feeding behavior in adolescents and young adults.